C-N-Codoped TiO2 Synthesis by using Peroxo Sol Gel Method for Photocatalytic Reduction of Cr(VI) - Diana Vanda Wellia; Dytta Fitria; Safni Safni (The Journal of Pure and Applied Chemistry Research, 2018)
C-N-codoped TiO2 (CNTO) photocatalysts were successfully synthesized by using “green” method peroxo sol-gel. XRD results revealed the presence of anatase phase only for all samples. The result of Scanning Electron Microscope-Electron Dispersive X-Ray (SEM-EDX) showed surface morphology of CNTO10 was spherical (44 nm) and homogeneous.  Diffuse Reflectance Spectra UV-Vis (DRS UV-Vis) result showed red shift in absorbance indicating successful modification of TiO2 by C and N. The result of photocatalytic activity in reducing Cr(VI) showed that  the Cr(VI) reduction  increase with the increase of irradiation time and photocatalyst’s mass.  The highest Cr(VI) reduction was 90.07% for CNTO10 sample. This is due to the synergistic effects of C and N dopants that improves  TiO2 photocatalytic activity under visible light irradiation.